2022
DOI: 10.1021/acs.nanolett.1c03786
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Delivery of Theranostic Nanoclusters for Lung Cancer Ferroptosis with Enhanced Chemodynamic/Radiation Synergistic Therapy

Abstract: Inefficient tumor accumulation and penetration remain as the main challenges to therapy efficacy of lung cancer. Local delivery of smart nanoclusters can increase drug penetration and provide superior antitumor effects than systemic routes. Here, we report self-assembled pH-sensitive superparamagnetic iron oxide nanoclusters (SPIONCs) that enhance in situ ferroptosis and apoptosis with radiotherapy and chemodynamic therapy. After pulmonary delivery in orthotopic lung cancer, SPIONCs disintegrate into smaller n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…Ultimately, ferroptosis ensued because IR and NPs exacerbated generation of hydroxyl radicals and tumor lipid peroxidation. 53 Additionally, this analysis demonstrated that SPIONCs have no effect on the level of blood biochemical and normal kidney and liver function and has the potential for clinical translation. 53 In addition, certain studies have employed nanomaterials as radionuclide carriers to supply sufficient tumor-targeted delivery and improve effect of radionuclide therapy.…”
Section: Combined Ferroptosis-driven Nanomaterials and Ionizing Radia...mentioning
confidence: 90%
See 1 more Smart Citation
“…Ultimately, ferroptosis ensued because IR and NPs exacerbated generation of hydroxyl radicals and tumor lipid peroxidation. 53 Additionally, this analysis demonstrated that SPIONCs have no effect on the level of blood biochemical and normal kidney and liver function and has the potential for clinical translation. 53 In addition, certain studies have employed nanomaterials as radionuclide carriers to supply sufficient tumor-targeted delivery and improve effect of radionuclide therapy.…”
Section: Combined Ferroptosis-driven Nanomaterials and Ionizing Radia...mentioning
confidence: 90%
“… 53 Additionally, this analysis demonstrated that SPIONCs have no effect on the level of blood biochemical and normal kidney and liver function and has the potential for clinical translation. 53 In addition, certain studies have employed nanomaterials as radionuclide carriers to supply sufficient tumor-targeted delivery and improve effect of radionuclide therapy. Chen et al utilized the therapeutic radionuclide iodine-131( 131 I) to label HSA-CAT nanoreactors (NRs), and dramatically attenuate tumor hypoxia, hence boosting the therapeutic efficacy of radionuclide 131 I.…”
Section: Combined Ferroptosis-driven Nanomaterials and Ionizing Radia...mentioning
confidence: 90%
“…Prussian blue/calcium peroxide nanocomposites promote iron mineralization in lung cancers, which greatly facilitates early diagnosis of lung carcinoma and activates ferroptosis to inhibit tumor growth [ 117 ]. Most recently, a self-assembled pH-sensitive superparamagnetic iron oxide nanoclusters (SPIONCs) is reported to enhance in situ ferroptosis and apoptosis of lung tumors with radiotherapy and chemodynamic therapy via releasing iron in the tumor microenvironment (TME) [ 118 ].…”
Section: The Role Of Ferroptosis In Pulmonary Diseasesmentioning
confidence: 99%
“…For example, the doxorubicin, bleomycin, or platinum coordination complexe causes mitochondrial DNA damage or prevent DNA synthesis by inducing cellular oxidative distress [ 47 , 48 ]. Furthermore, genetically unstable clones generated upon irradiation also displayed higher intracellular ROS levels, potentially due to reduced mitochondrial activity and respiration [ 49 , 50 ]. In addition, cancer cells under hypoxia are associated with an increase in ROS, likely because of the deficiency in O 2 that prevents electron transfer across the mitochondrial complexes, thereby increasing the possibility of electron leakage to generate ROS [ 27 , 51 , 52 ].…”
Section: Oxidative Stress In Cancer Cellsmentioning
confidence: 99%